Turnover intention pada karyawan telework: Tinjauan literatur sistematis - Evi; Rizkya Dwi Safitri; Chusnul Kotimah (Cognicia, 2023)
The currently developing telework phenomenon has many impacts on employees, one of the impacts of implementing telework is turnover intention. This research was conducted with the aim of knowing the dynamics of telework employees who tend to turnover intention. The method used in this research is a systematic literature review referring to 15 journal articles obtained from the Google Scholar, Scopus, and PubMed databases. The results of the literature review that has been carried out show that telework related to turnover intention. Several things were found that showed a link between telework and turnover intentions, including: 1) Specific job characteristics of the telework gap felt by employees are additional drivers of turnover intentions and can be mediated by jealousy and job dissatisfaction. 2) Differences in perceptions of remote work from each employee's perspective may increase feelings of envy toward remote workers and job dissatisfaction, which in turn is associated with higher turnover intentions and poorer job performance. 3) The implications of remote work as a flexible work arrangement on work outcomes, highlighting the negative impact on employee well-being and behavior such as turnover intentions. Keywords: Employees, systematic literature review, telework, turnover intention